Tracking fungal growth: establishment of Arp1 as a marker for polarity establishment and active hyphal growth in filamentous ascomycetes - Groth, Anika; Schunke, Carolin; Reschka, Eva Johanna; Pöggeler, Stefanie; Nordzieke, Daniela Elisabeth (Journal of Fungi, 2021)
Polar growth is a key characteristic of all filamentous fungi. It allows these eukaryotes to not only effectively explore organic matter but also interact within its own colony, mating partners, and hosts. Therefore, a detailed understanding of the dynamics in polar growth establishment and maintenance is crucial for several fields of fungal research. We developed a new marker protein, the actin-related protein 1 (Arp1) fused to red and green fluorescent proteins, which allows for the tracking of polar axis establishment and active hyphal growth in microscopy approaches. To exclude a probable redundancy with known polarity markers, we compared the localizations of the Spitzenkörper (SPK) and Arp1 using an FM4-64 staining approach. As we show in applications with the coprophilous fungus Sordaria macrospora and the hemibiotrophic plant pathogen Colletotrichum graminicola, the monitoring of Arp1 can be used for detailed studies of hyphal growth dynamics and ascospore germination, the interpretation of chemotropic growth processes, and the tracking of elongating penetration pegs into plant material. Since the Arp1 marker showed the same dynamics in both fungi tested, we believe this marker can be broadly applied in fungal research to study the manifold polar growth processes determining fungal life.